A mapping system for the integration of OWL-DL ontologies. - Haase, P; Motik, B (ACM, 2005)
To enable interoperability between applications in distributed information systems based on heterogeneous ontologies, it is necessary to formally define the notion of a mapping between ontologies. In this paper, we define a mapping system for OWL-DL ontologies, where mappings are expressed as correspondences between conjunctive queries over ontologies. As query answering within such a general mapping system is undecidable, we identify a decidable fragment of the mapping system, which corresponds to OWL-DL extended with DL-safe rules. We further show how the mapping system can be applied for the task of ontology integration and present a query answering algorithm. Copyright 2005 ACM.